PENGELOLAAN SAMPAH BERBASIS MASYARAKAT MELALUI BANK SAMPAH - Saputro, Yusa Eko; Kismartini, Kismartini; Syafrudin, Syafrudin (Badan Pengembang Konservasi UNNES, 2015)
Implementation of waste banks in principle is one of social engineering to urge people to sort out waste. Through the waste bank finally found one innovative solution to